Approaches to Disaster Management Examining the Implications of Hazards, Emergencies and Disasters - Tiefenbacher, John (IntechOpen, 2013)
Approaches to Disaster Management regards critical disaster management issues. Ten original research reports by international scholars centered on disaster management are organized into three general areas of hazards and disaster management. The first section includes discussions of perspectives on vulnerability and on evolving approaches to mitigation. The second section highlights approaches to improve data use and information management in several distinct applications intended to promote prediction and communication of hazard. The third section regards the management of crises and post-event recovery in the private sector, in the design of urban space and among the victims of disaster. This volume contributes both conceptual and practical commentary to the disaster management literature.